Relationship of P-Selectin Glycoprotein Ligand-1 to Prognosis in Patients With Multiple Myeloma - (:unkn) unknown (CIG MEDIA GROUP, LP, 2015)
The aim of the present study was to investigate the relationship between PSGL-1 expression in the bone marrow and the known prognostic factors for multiple myeloma disease, disease stage, and survival. D162 staining and the staining degree, with the other standard immunohistochemical stains, were shown to be beneficial in the diagnosis of multiple myeloma disease. However, the results did not provide information about the disease course. Background: Changes occur in adhesion molecules in the disease course of multiple myeloma. P-selectin glycoprotein ligand-1 (PSGL-1, CD162) works as the ligand of selectin-neutrophil adhesion molecules. The aim of the present study was to investigate the relationship between PSGL-1 expression in the bone marrow and the known prognostic factors for multiple myeloma disease, disease stage, and survival. Materials and Methods: This research included 63 patients with multiple myeloma (26 women [41.3%]; 37 men [58.7%]). The bone marrow biopsy samples obtained at disease diagnosis for each patient were stained imniunohistochemically in terms of CD162 expression using standard diagnostic immunohistochemical staining methods. The laboratory results, CD162 expression, overall survival, demographic characteristics of the disease, and the relationship between CD162 expression and the disease stage were evaluated. Results: Among the 63 patients included in the present study, the survival rate was 82.3% for 1 year, 73.2% for 2 years, 63.4% for 3 years, 51.7% for 4 years, 40.3% for 5 years, and 33.6% for 6 and 7 years. A statistically significant difference was not detected between the CD162 staining ratio and disease survival (P = .232). A statistically significant difference was not detected between the CD162 staining degree and survival rate (P = .184). However, the overall survival of the patients with no CD162 expression in the bone marrow was lower than that for the patients whose CD162 was stained 1, 2, and 3 degrees (12.33 +/- 11.49, 28.65 +/- 31.44, 37.25 +/- 29.32, and 47.92 +/- 45.29 months, respectively; P < .001). Conclusion: In the present study, CD162 staining and the staining degree, with the other standard immunohistochemical stains, were shown to be beneficial in the diagnosis of multiple myeloma disease. However, the results did not provide information about the disease course. Studies of a larger number of patients to examine P-selectin and interleukin-6 levels are needed to investigate the disease course.
Keywords: CD162; Immunocytochemistry; Multiple myeloma; Prognosis; P-selectin ligand protein; TUMOR MICROENVIRONMENT; CELLS; IDENTIFICATION; INTERLEUKIN-6; METASTASIS; PLATELETS; SURVIVAL; GROWTH